2011
DOI: 10.1021/ol200860t
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Selective Defluorination to Generate Partially Fluorinated Biaryls

Abstract: A Ni-catalyzed, chemoselective cross-coupling reaction of polyfluoroarenes under mild reaction conditions is reported. A variety of fluorine-containing biaryls are synthesized in good-to-excellent yields. A wide range of substitution patterns and functional groups are tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Thus, hydrodefluorination or cross coupling reactions can provide fluorinated building blocks, which are often not accessible otherwise . However, catalytic C-F bond functionalization reactions of highly fluorinated aromatic precursors via cross coupling reactions are still rare [4,14,17,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Radius et al reported an initial and exceptional example of a nickelmediated Suzuki-Miyaura cross coupling reaction of perfluorotoluene with aryl boronic acids on using a nickel(II) carbene complex as catalyst [25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, hydrodefluorination or cross coupling reactions can provide fluorinated building blocks, which are often not accessible otherwise . However, catalytic C-F bond functionalization reactions of highly fluorinated aromatic precursors via cross coupling reactions are still rare [4,14,17,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Radius et al reported an initial and exceptional example of a nickelmediated Suzuki-Miyaura cross coupling reaction of perfluorotoluene with aryl boronic acids on using a nickel(II) carbene complex as catalyst [25].…”
Section: Introductionmentioning
confidence: 99%
“…62) [115]. The reaction proceeds under mild reaction conditions and is tolerant to a range of boronic acids of varying electronic nature.…”
Section: ð61þmentioning
confidence: 99%
“…Most of the reported Suzuki-Miyaura type cross-coupling reactions via C-F bond cleavage, employing either highly electron-deficient organofluorine compounds or those bearing a directing group, have traditionally been conducted in the presence of a base [59,[75][76][77][78][79][80][81][82][83][84][85], whereas fluoride anion itself is regarded as a good activator for neutral organoboron reagents. The role of a base in a Suzuki-Miyaura coupling reaction is generally considered to follow one of two patterns; either converting a neutral organoboron compound into a nucleophilic boronate, or converting a palladium halide intermediate into an active palladium species via a ligand exchange reaction by the base [86,87].…”
Section: Pd(0)-catalyzed Cross-coupling Reactions Of Tetrafluoroethylmentioning
confidence: 99%